Reconstruction of Abdominal Wall Defects Using a Pedicled Anterolateral Thigh Flap including the Vastus Lateralis Muscle: A Report of Two Cases - Kiyoko Fukui; Masaki Fujioka; Satoko Ishiyama (Case Reports in Surgery)
The purpose of abdominal wall reconstruction is to prevent hernias and protect the abdominal viscera. In cases involving full-thickness defects of the rectus abdominis muscle, the muscle layer should be repaired. We present 2 cases in which full-thickness lower rectus abdominis muscle defects were reconstructed using vastus lateralis-anterolateral thigh flaps. The pedicled vastus lateralis-anterolateral thigh flap provides skin, fascia, and muscle tissue. Furthermore, it has a long neurovascular pedicle and can reach up to the periumbilical area and cover large defects. We consider that this muscle flap is a good option for repairing full-thickness lower abdominal defects.